Pengaruh Locus of Control dan Self Efficacy terhadap Kinerja Karyawan dengan Employee Engagement sebagai Variabel Moderasi - Silvia Hendriyani; Dikdik Harjadi; Dede Djuniardi (Jurnal Syntax Admiration, 2024)
Objectives of the study: 1) Knowing the influence of Locus Of Control on the performance of Grand Yogya Majalengka employees. 2) Knowing the effect of Self Efficacy on the performance of Grand Yogya Majalengka employees. 3) Knowing the effect of Locus Of Control on the performance of Grand Yogya Majalengka employees with Employee Engagement as a moderation variable. 4) Knowing the effect of Self Efficacy on the performance of Grand Yogya Majalengka employees with Employee Engagement as a moderation variable. The sample in this study was 150 employees of Grand Yogya Majalengka using the Proportionate Stratified Random Sampling technique. Data was analyzed by Moderated Regression Analysis using SPSS 25. The results of this study: 1) Locus of Control has a positive and significant effect on employee performance. 2) Self Efficacy has a positive and significant effect on employee performance. 3) Employee engagement can moderate the effect of Locus of control on employee performance. 4). Employee engagement can moderate Self Efficacy of employee performance.